Kinetic quantification of plyometric exercise intensity - Ebben, W. P.; Fauth, M. L.; Garceau, L. R.; Petushek, E. J. (The Journal of Strength and Conditioning Research, 2011)
Quantification of plyometric exercise intensity is necessary to understand the characteristics of these exercises and the proper progression of this mode of exercise. The purpose of this study was to assess the kinetic characteristics of a variety of plyometric exercises. This study also sought to assess gender differences in these variables. Twenty-six men and 23 women with previous experience in performing plyometric training served as subjects. The subjects performed a variety of plyometric exercises including line hops, 15.24-cm cone hops, squat jumps, tuck jumps, countermovement jumps (CMJs), loaded CMJs equal to 30% of 1 repetition maximum squat, depth jumps normalized to the subject's jump height (JH), and single leg jumps. All plyometric exercises were assessed with a force platform. Outcome variables associated with the takeoff, airborne, and landing phase of each plyometric exercise were evaluated. These variables included the peak vertical ground reaction force (GRF) during takeoff, the time to takeoff, flight time, JH, peak power, landing rate of force development, and peak vertical GRF during landing. A 2-way mixed analysis of variance with repeated measures for plyometric exercise type demonstrated main effects for exercise type and all outcome variables (p <= 0.05) and for the interaction between gender and peak vertical GRF during takeoff (p <= 0.05). Bonferroni-adjusted pairwise comparisons identified a number of differences between the plyometric exercises for the outcome variables assessed (p <= 0.05). These findings can be used to guide the progression of plyometric training by incorporating exercises of increasing intensity over the course of a program.